Community standards for open cell migration data. Issue 5 (12th May 2020) - Gonzalez-Beltran, Alejandra N; Masuzzo, Paola; Ampe, Christophe; Bakker, Gert-Jan; Besson, Sébastien; Eibl, Robert H; Friedl, Peter; Gunzer, Matthias; Kittisopikul, Mark; Dévédec, Sylvia E Le; Leo, Simone; Moore, Josh; et al.
Abstract: Cell migration research has become a high-content field. However, the quantitative information encapsulated in these complex and high-dimensional datasets is not fully exploited owing to the diversity of experimental protocols and non-standardized output formats. In addition, typically the datasets are not open for reuse. Making the data open and Findable, Accessible, Interoperable, and Reusable (FAIR) will enable meta-analysis, data integration, and data mining. Standardized data formats and controlled vocabularies are essential for building a suitable infrastructure for that purpose but are not available in the cell migration domain. We here present standardization efforts by the Cell Migration Standardisation Organisation (CMSO), an open community-driven organization to facilitate the development of standards for cell migration data. This work will foster the development of improved algorithms and tools and enable secondary analysis of public datasets, ultimately unlocking new knowledge of the complex biological process of cell migration.